LINGUISTIC LANDSCAPE OF DISASTER SIGNS IN PADANG CITY, WEST SUMATRA: A MULTIMODAL ANALYSIS - Denil, Mauli; Naniana Nimrod Benu; Yendra; Melyanda Agustin Chairina (Curricula: Journal of Teaching and Learning, 2025)
This study aims to analyze disaster warning signs in Padang City, West Sumatra, using a multimodal approach within the framework of linguistic landscape studies. As a disaster-prone area vulnerable to earthquakes and tsunamis, Padang provides a critical context to examine the effectiveness of visual and verbal communication in disaster warning systems. Data were collected through field observations and visual documentation of disaster signs in strategic locations. The findings reveal that these signs combine linguistic elements (monolingual and bilingual), visual components (symbols, colors, images), and strategic placement following national regulations. Symbols such as tsunami waves, tall buildings, and evacuation arrows enhance public understanding. However, the current signage design lacks inclusivity for vulnerable groups such as the elderly and persons with disabilities. Moreover, the integration of local cultural context and indigenous knowledge remains limited. This study emphasizes the importance of a holistic and inclusive approach to disaster signage design,one that not only complies with technical standards but also considers the social, cultural, and psychological dimensions of the community. The findings offer valuable insights for improving disaster communication systems to be more effective and adaptive for multilingual and multicultural societies.